Clinical Decision-Making of Artificial Intelligence vs Medical Professionals in Patients With Syncope - van Zanten, Steven; Boel, Thomas T; de Jong, Jelle Sy; Bais, Babette; Fedorowski, Artur ; 0000-0002-5352-6327; Sutton, Richard; Selder, Jasper L; Giele, Freek; Geertsma, Christiaan; Scheffer, Mike G; de Groot, Joris R; de Lange, Frederik J (JACC: Advances, 2025)
BACKGROUND: Artificial intelligence may improve diagnostic yield and accuracy in syncope. OBJECTIVES: The purpose of this study was to compare Generative Pretrained Transformer 4-Omni (GPT-4o) with medical professionals (MPs) in establishing syncope diagnoses and recommending interventions based on general practitioner's referral letters to a syncope-unit. METHODS: This three-phase study evaluated 55 anonymized referral letters. Phase-1: GPT-4o and MPs (12 physicians, 6 allied professionals) provided differential diagnoses. In Phase-2: all patients underwent 1.5 years of follow-up for recurrences and additional investigations. In Phase-3: a multidisciplinary committee established final diagnoses by adjudication. Diagnostic performance was assessed using a custom Diagnostic Precision Score (DPS), penalizing incorrect differential diagnoses from Phase-1. GPT-4o was tested in a privacy-safe environment and instructed with European Society of Cardiology guidelines. RESULTS: Fifty-five letters were independently analyzed once by each of the eighteen MPs and by GPT-4o, yielding 1,045 assessments. Diagnostic yield, defined as any suggestion of a diagnosis, was 81.9% for physicians, 84.5% allied professionals, and 100% GPT-4o. Diagnostic performance, defined as the presence of the final diagnosis in the initial differential diagnosis, was 75.9% for GPT-4o, 48.6% and 36.7% for physicians and allied professionals. DPS was 22.9% for physicians (148.75/648), 12.6% for allied professionals (40.75/324), and -6.9% for GPT-4o (-4.00/54). GPT-4o incorrectly labeled 3 of 4 cardiac diagnoses as reflex syncope. GPT-4o, but not MPs, suggested additional lifestyle measures such as counterpressure maneuvers (29/55; 52.7%) and increased fluid intake (28/55; 50.9%). CONCLUSIONS: GPT-4o proposed a diagnosis in all cases; however, with a low DPS and is not yet suitable for unsupervised clinical use interpreting referral letters.
Copyright © 2026 The Authors. Published by Elsevier Inc. All rights reserved.